Topical formulations containing Copaifera duckei Dwyer oleoresin improve cutaneous wound healing - Goncalves Dias, Fernanda Gosuen; Pereira, Lucas de Freitas; Furtado, Ricardo Andrade; Magalhaes, Georgia Mode; Miguel, Marina Pacheco; Gosuen Goncalves Dias, Luis Gustavo [UNESP]; Jorge, Adriana Torrecilhas; Honsho, Cristiane dos Santos; Ambrosio, Sergio Ricardo; Bastos, Jairo Kenupp; Carrijo, Micaela Silva; Tavares, Denise Crispim (Mashhad Univ Med Sciences, 2021)
Objective: Evaluation of the healing and toxicological effects of Copaifera duckei Dwyer oleoresin (CDO). Materials and Methods: Rodents with skin lesions were divided into nine groups, including daily treatments with 1, 3 and 10% CDO, collagenase, antibiotic ointment and control groups, for 14 days. Results: Treatment with 10% CDO reduced skin edema and hyperplasia, demonstrating anti-inflammatory effect of the oil. Reduction in the wound area was observed, indicating the healing effect of CDO. Histopathological analysis showed increases in angiogenesis and re-epithelialization in animals treated with the highest concentration. On the other hand, no alterations in ulcerations, inflammatory infiltrate, hemorrhage, congestion, degeneration, percentage of collagen fibers, number of cells stained with anti-macrophage migration inhibitory factor, or density of area stained with anti-collagen I and III were found. Toxicogenetic analysis revealed no differences in micronucleus frequencies or in the ratio of polychromatic eiythrocytes to total eiythrocytes between treated and negative control, demonstrating the absence of genotoxicity and cytotoxicity, respectively. There was no difference in levels of liver enzymes among groups, indicating the absence of hepatotoxicity. Conclusion: Formulations of CDO exerted beneficial effects on the stages of cutaneous wound healing and are promising options for the treatment of wounds.
Keywords: Cutaneous wound healing; Copaifera duckei Dwyer oleoresin; Toxicity